Anaesthetic Efficacy of 4% Articaine in Comparison with 2% Lidocaine as Intraligamentary Injections after an Ineffective Inferior Alveolar Nerve Block in Mandibular Molars with Irreversible Pulpitis: A Prospective Randomised Triple-Blind Clinical Trial - Nazanin Zargar; Elnaz Shooshtari; Leila Pourmusavi; Alireza Akbarzadeh Baghban; Hengameh Ashraf; Ardavan Parhizkar (Pain Research and Management)
The objective of the current study was to compare the anaesthetic efficacy of supplemental intraligamentary (IL) injection of 4% articaine with that of 2% lidocaine in the mandibular first and second molars with irreversible pulpitis after an ineffective inferior alveolar nerve block injection (IANB) using the same anaesthetic in a randomised triple-blind clinical trial. Seventy-six adult patients, who were diagnosed with irreversible pulpitis in the mandibular first or second molars, were divided into 2 groups and received IANB randomly. In patients with lip numbness, anaesthesia was evaluated with the cold and electrical pulp (EPT) tests, and if the reported number on EPT was below 100, supplemental IL injection was administered using the same anaesthetic. The teeth were retested after 5 minutes. The Heft–Parker visual analogue scale was used to evaluate pain after IANB and IL injections. Statistical analysis was performed using repeated measures ANOVA, chi-square, and independent-sample and paired-sample t-tests. The results showed that there was no significant difference in the success rates of supplemental IL and IANB injections between articaine and lidocaine. Furthermore, there was no significant difference in the success rates of supplemental IL injection with lidocaine between the mandibular first and second molars. However, there was a significant difference in the success rates of supplemental IL injection with articaine between the mandibular first and second molars. Moreover, supplemental IL injections indicated no significant difference in the anaesthetic efficacy between articaine and lidocaine; nevertheless, they were more effective in the mandibular second molars, especially with articaine.